Respon Pertumbuhan dan Hasil Tanaman Melon (Cucumis melo L.) Terhadap Pemberian Kotoran Hewan Ayam dan Trichoderma sp. - Khumairoh, Diah Kurnia Nur; Serdani, Army Dita; Wibowo, Agung Setya; Puspitorini, Palupi (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Melon (Cucumis melo L.) is one of the most widely cultivated plants because it is very profitable. The purpose of this study was to determine how chicken manure and the right dose of Trichoderma sp. contribute to increasing the growth and yield of melon plants. In this study, a Randomized Block Design (RAK) was arranged factorially and consisted of two factors. The first factor was the comparison of chicken manure, which included the variables V0 (Without Trichoderma sp. Treatment), V1 (Trichoderma sp. 5 g/L), V2 (Trichoderma sp. 10 g/L), and V3 (Trichoderma sp. 15 g/L). Some of the parameters used in this study include leaf blades, stem diameter, leaf area, fruit weight, and fruit diameter. Data were analyzed statistically using analysis of variance (ANOVA) followed by Duncan's Test at a level of 5%. The experiment was conducted at the UNISBA Blitar Greenhouse, Sananwetan District, Blitar City, East Java in September - November 2024. Based on the results of the study, the best treatment combination was the T2V3 treatment combination (Blotong + Chicken Kohe 4: 2 with Trichoderma sp. 15 g / L). This treatment combination was able to increase growth and yields from the vegetative phase to the generative phase in melon plants.